Research Progress in Atopic March - Yang, Lan; Fu, Jinrong; Zhou, Yufeng (Frontiers in Immunology, 2020)
The incidence of allergic diseases continues to rise. Cross-sectional and longitudinal studies have indicated that allergic diseases occur in a time-based order: from atopic dermatitis and food allergy in infancy to gradual development into allergic asthma and allergic rhinitis in childhood. This phenomenon is defined as the “atopic march”. Some scholars have suggested that the atopic march does not progress completely in a temporal pattern with genetic and environmental factors. Also, the mechanisms underlying the atopic march are incompletely understood. Nevertheless, the concept of the atopic march provides a new perspective for the mechanistic research, prediction, prevention, and treatment of atopic diseases. Here, we review the epidemiology, related diseases, mechanistic studies, and treatment strategies for the atopic march.